Gastrointestinal Conditions in Rheumatoid Arthritis Patients - Toirov Doston Rustamovich; Khusainova Munira Alisherovna; Khaydarov Sanjar Nizamitdinovich; Kamolova Diyora Djamshedovna (Zien Journals, 2022)
Rheumatoid arthritis (RA) is a serious medical and social problem, characterised by a steadily progressive disorganisation of the connective tissue, based on profound immunopathological changes with autoaggressive features. RA ranks first in terms of prevalence among inflammatory diseases of the joints. The social significance of this disease is determined not only by its high prevalence, but also by the great material damage caused to society, the patient and his family due to the high incapacity and early onset of disability. Steady progression of the pathological process despite the use of modern therapeutic methods results not only in significant functional insufficiency of the locomotor apparatus but also in the shortening of the patients' life span by 4-10 years and the increase of the death rate which exceeds that of the general population. The prognosis of RA patients with systemic manifestations is particularly unfavorable: generalized vasculitis, rheumatoid nodules, lymphoadenopathy, lung, heart, liver, kidney and other organs and systems are affected. Among the extra-articular manifestations of RA, gastrointestinal (GI) lesions are the least studied, although the most severe process, intestinal amyloidosis, is well known, occurring in 11% of patients and usually combined with amyloidosis of other internal organs.
Keywords: Rheumatoid arthritis; inflammatory diseases; gastrointestinal